2004
DOI: 10.1515/sg-2004-0034
|View full text |Cite
|
Sign up to set email alerts
|

Seed Source Variation in Growth Performance and Oil Yield of Jatropha curcas Linn. in Central India

Abstract: Results of a seed source evaluation trial of Jatropha curcas Linn. laid out in 1996 at Jabalpur (M.P), a semi arid region of India are reported and discussed. Seeds collected from ten sources from central India representing the states Madhya Pradesh and Maharashtra viz. Gondia, Bichia, Balaghat, Niwas, Khandwa, Burhanpur, Nasik, Chindwara, Kundam and Jabalpur were evaluated for their growth performance from nursery stage (3 months) to field (two years). Variation in seed oil content of different sources were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
60
3
14

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(87 citation statements)
references
References 1 publication
(1 reference statement)
10
60
3
14
Order By: Relevance
“…Abreu et al (2009) também encontraram variabilidade genética significativa, entre dez acessos avaliados quanto à altura de plantas, altura de inserção da primeira folha, ao diâmetro do colo e ao número de folhas. Ginwal et al (2004) avaliaram acessos de pinhão-manso procedentes de dez Estados da Índia, dos três meses aos dois anos, e encontraram variabilidade genética em características como: morfologia da semente, características de crescimento e produtividade de óleo. Parthiban et al (2011) avaliaram 27 híbridos de pinhão-manso na Índia e econtrataram altos coeficientes de variação fenotípica e genotípica, em que a produção de sementes foi o caráter com os maiores coeficientes de variação, seguido por índice de robustez, NRS, DC, AP e número de ramos primários.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Abreu et al (2009) também encontraram variabilidade genética significativa, entre dez acessos avaliados quanto à altura de plantas, altura de inserção da primeira folha, ao diâmetro do colo e ao número de folhas. Ginwal et al (2004) avaliaram acessos de pinhão-manso procedentes de dez Estados da Índia, dos três meses aos dois anos, e encontraram variabilidade genética em características como: morfologia da semente, características de crescimento e produtividade de óleo. Parthiban et al (2011) avaliaram 27 híbridos de pinhão-manso na Índia e econtrataram altos coeficientes de variação fenotípica e genotípica, em que a produção de sementes foi o caráter com os maiores coeficientes de variação, seguido por índice de robustez, NRS, DC, AP e número de ramos primários.…”
Section: Resultsunclassified
“…Quanto a DC, estimativas de herdabilidade altas a moderadas têm sido relatadas, com valores de: 33,7% (Laviola et al, 2011), 68,9% (Das et al, 2010), 76% (Ginwal et al, 2004) e 87,1% (Parthiban et al, 2011); contra 85,50% do presente trabalho.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Fey et al (2014) also found a positive correlation between height and production (0.72). As all the features have a positive effect on each other, the improvement of one characteristic will result in improvement of others which the first has positive correlation (GINWAL et al, 2004). Among them, the variable that has more influence on grain production is the canopy projection on inter rows, that also has effect on the canopy volume.…”
Section: Resultsmentioning
confidence: 99%
“…Kelima genotype unggul jarak pagar yang diuji dalam penelitian ini merupakan populasi terperbaiki (Improved Population) melalui seleksi massa dari populasi liar yang ada hubungan kekerabatannya satu sama lainnya, terutama daerah asal (provenan). Ditambahkan oleh Ginwal et al (2004) Sehubungan dengan tidak adanya beda nyata pertumbuhan dan perkembangan akar kelima genotype unggul yang diuji dalam penelitian ini, dan berdasarkan pada data Tabel 1 hingga Tabel 7, maka dapat diuraikan bahasan sebagai berikut ini. Arsitektur perakaran kelima genotype unggul jarak pagar yang diuji dari sejak awal perkembangannya hingga tanaman muda berumur 6 bulan menunjukkan arsitektur yang unik, akar tunggang yang tumbuh geotropik dengan empat akar lateral yang tumbuh horizontal.…”
Section: Hasil Dan Pembahasanunclassified